Breakage behaviour and functionality of spray-dried agglomerated model infant milk formula: Effect of proteins and carbohydrates content. (15th October 2022) - Han, Jie; Fitzpatrick, John; Cronin, Kevin; Maidannyk, Valentyn; Miao, Song
Highlights: Formulation impacts breakage by affecting physical properties of model powders. The influence of proteins on breakage was greater than that of carbohydrates. Whey protein powders were bigger, more irregular, and had weaker structures. Sucrose powders were bigger than pure lactose and maltodextrin powders. Whey protein powder had better rehydration properties but suffered more breakage. Abstract: This study explored the effect of protein content (whey protein and casein) and carbohydrate content (lactose, sucrose, and maltodextrin) on the breakage behaviour and its influence on spray-dried agglomerated model infant milk formula. Whey protein powders were bigger in particle size, weaker in structural strength, and marginally more irregular in shape, which resulted in better rehydration properties but more breakage than pure casein powders. Similarly, sucrose samples had better rehydration properties and higher glass transition temperatures but suffered more breakage than maltodextrin and pure lactose powders because of their bigger particle size. The influence of proteins on breakage was greater than that of carbohydrates. Breakage changed the physical and structural properties of powders, especially for whey protein and sucrose samples, which caused the deterioration of rehydration properties and the decrease in crystallization temperatures. From the perspective of particle breakage, unwanted dairy powder breakage could be controlled by changing powder formulations.